Peran Intellectual Capital terhadap Keunggulan Bersaing UMKM Kuliner Makanan Ringan di Kota Semarang (Eksplorasi Pengaruh Managerial capability, Market Knowledge Capability, dan Innovation Capability) - Eka Yulianti; Muhammad Feriady (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study seeks to examine the role of intellectual capital in the competitive advantage of culinary MSMEs in Semarang City, with a focus on managerial capability, market knowledge competence, and innovation capability. This study takes a quantitative approach, surveying 156 culinary MSMEs in Semarang City. The data were analyzed using multiple linear regression and the SPSS application. The findings indicate that managerial competencies, market knowledge competence, and innovation capability all have a favorable and significant impact on the competitive advantage of culinary MSMEs. The most influential variable is innovation capability. This study's findings support the Knowledge-Based View approach, which stresses knowledge management and knowledge-based competencies as sources of competitive advantage. This study has practical significance for MSME players and policymakers formulating MSME development policies aimed at boosting intellectual capital.